SCIENCE IS YOUTH WORK (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The science of physics contributes to the development of human civilization, improving living standards, and has the most important factors in promoting science and technology to new levels. There is no periodicity in the development of science and modern technologies, in raising people's living standards. To achieve success, qualities such as hard work and hard work arerequired of youngpeople. The purpose of this article is to motivate young people embarking on